Studi Pemikiran Jamal Al Banna tentang Talak - Siti Khoirotul Ula (MAHAKIM Journal of Islamic Family Law, 2017)
In divorce, by the classical Jurist of fiqh, husbands may unilaterally divorce (talak) without making a dialogue with their wives first. Many contemporary thinkers, especially moslem feminists, assumed that is affected by gender inequality which is a cultural product not pure of Islamic values. Moreover, the fact that the classical Jurists of Fiqh are dominated by men, so the existing of fiqh are patriarchal and masculine pattern. One of the most contemporary moslem thinkers of Gender concerns is Jamal al-Banna, a moslem thinker from Egypt. Then, this article is written to describe Jamal al-Banna’s mindset about divorce. Based on his opinion, he stated that husband cannot say to divorce without the agreement (qabul) of his wife as marriage is a transparent relation symbolized by ijab- qabul contract and also testimonial (syahadah). Therefore, if the agreement is destroyed by divorce, all elements of marriage contract must know. Thus, one-sided divorce by husband is unacceptable. Divorce is acceptable if both of husband dan wife have the agreement. He formulated the rules of divorce, referring to Al-Baqarah verse 229 in which his interpretation is the equality between husband and wife about divorce. His educational background of trading school may influenced his mindset mostly. So, he assumed about the similarity of marriage contract and trading contract in which if a marriage will be destroyed by divorce, both of husband and wife must have the same agreement.